ELECTRICITY DEMAND AND SUPPLY PROJECTION IN WEST KALIMANTAN PROVINCE - B61111048, SUGIYANTA (Jurnal Ekonomi Daerah (JEDA), 2015)
The aim of this research are to fetch electricity demand and supply projection in West Kalimantan until 2020 as well as the (1) electricity demand projection for household, business, industrial and public sector, (2) to know the electricity supply projection from PT PLN power plants in West Kalimantan region, (3) to know the electricity demand projection per regency/city in West Kalimantan Province, and (4) to map the investment needs for power plants, transmission networks and distribution networks. The method of this research is a projection method using Long-range Energi Alternative Planning (LEAP) software. The result of this researchare electricity demand projection per sector until 2020 in West Kalimantan is varied. (1) Electricity demand for household sector is 1.997 GWh, business sector 625 GWh, industrial sector 565 GWh, and public sector 125 GWh. (2)Electricity supply from PT. PLN in West Kalimantan Region is 676 MW. (3) The highest electricity demand for household sector is 414 GWh in Pontianak City and the lowest demand is 30 GWh in Kayong Utara Regency. (4) Finally, Total investment needs is US$ 1785,6 million. Keywords : Projection, Electricity